An alternative method for meta-analysis - Joachim Hartung (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1998)
In many fields of applications, test statistics are obtained by combining estimates from several experiments, studies or centres of a multicentre trial. The commonly used test procedure to judge the evidence of a common overall effect can result in a considerable overestimation of the significance level, leading to a high rate of too liberal decisions. An alternative test statistic is presented and a better approximating test distribution is derived. Explicitely discussed are the methods in the unbalanced heteroscedastic, way random ANOVA model and for the probability difference method including interaction treatment by centres. Numerical results are presented by simulation studies.
Keywords: 519; meta-analysis; combining experiments; multi-centre study; interaction treatment by centres; heteroscedastic ANOVA model; random effects; probability difference method